2021
DOI: 10.1007/s13346-021-01011-7
|View full text |Cite
|
Sign up to set email alerts
|

Spray-dried lactose-leucine microparticles for pulmonary delivery of antimycobacterial nanopharmaceuticals

Abstract: Pulmonary delivery of nanocarriers for novel antimycobacterial compounds is challenging because the aerodynamic properties of nanomaterials are sub-optimal for such purposes. Here, we report the development of dry powder formulations for nanocarriers containing benzothiazinone 043 (BTZ) or levofloxacin (LVX), respectively. The intricacy is to generate dry powder aerosols with adequate aerodynamic properties while maintaining both nanostructural integrity and compound activity until reaching the deeper lung com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 38 publications
1
9
0
2
Order By: Relevance
“…The DPI formulations of CAF®01-T/D (30:70) prepared with leucine displayed non-significantly higher size and PDI with increasing concentrations of leucine. Prior studies have reported an increased particle size of liposomes after spray drying with L-leucine and lactose (Mangal et al, 2015;Thiyagarajan et al, 2021) due to aggregation in the dissolved microparticle samples (Thiyagarajan et al, 2021). In our recent study with DPI formulations of lipid-polymer hybrid nanoparticles spray-dried with a combination of trehalose, dextran and leucine, we also observed a slight increase in the particle size of nanoparticles after spray drying (Xu et al, 2022a).…”
Section: Discussionsupporting
confidence: 64%
“…The DPI formulations of CAF®01-T/D (30:70) prepared with leucine displayed non-significantly higher size and PDI with increasing concentrations of leucine. Prior studies have reported an increased particle size of liposomes after spray drying with L-leucine and lactose (Mangal et al, 2015;Thiyagarajan et al, 2021) due to aggregation in the dissolved microparticle samples (Thiyagarajan et al, 2021). In our recent study with DPI formulations of lipid-polymer hybrid nanoparticles spray-dried with a combination of trehalose, dextran and leucine, we also observed a slight increase in the particle size of nanoparticles after spray drying (Xu et al, 2022a).…”
Section: Discussionsupporting
confidence: 64%
“…Lactose and leucine were selected as well‐established excipients for dry‐powder formulations. [ 26 ] When the concentrations of lactose and leucine were optimized to 2.5% or 1% w/v, respectively, stable microparticles with a high fine‐particle fraction were achieved. To determine its aerodynamic properties after adding BDQ‐loaded liposomes, the microparticles were investigated using a next‐generation impactor.…”
Section: Resultsmentioning
confidence: 99%
“…Ter domínio das técnicas de aerolização dos lipossomas é importante para garantir um produto com qualidade segundo as especificações (Ran, et al, 2015), uma vez que através destas técnicas é possível preservar a integridade do nanocarreador e minimizar as interações físico-químicas que causam a agregação das partículas (Thiyagarajan, et al, 2021). As técnicas de aerolização mais utilizadas são Spray Drying, Spray Freeze Drying e Freeze Drying (Misra, et al,2009).…”
Section: Técnicas De Aerolização De Lipossomasunclassified